2012
DOI: 10.1002/jmv.23254
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of Th17 cells in the peripheral blood of children infected with enterovirus 71

Abstract: Enterovirus 71 (EV71) affects the health of young children globally causing severe neurologic diseases. The relationship between EV71 infection and T helper type 17 (Th17) has not been described, although this new Th subset or interleukin-17 (IL-17) has been reported to be associated with other viral infections. The purpose of the current study was to describe the immune profile involving Th17 cells, neutrophils, and related factors and to speculate on the possible immunopathogenesis of EV71 infections. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
9
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
6
9
2
Order By: Relevance
“…Based on these findings, the imbalance of Th1/Th2 cells may stimulated by HFMD, while the Th17/Treg imbalance may play a decisive function in HFMD progression. These findings are consistent with a previous study by Chen et al, which identified that Th17 cells increased significantly in children with HFMD, suggesting that Th17-mediated immune response plays a crucial role in the progression of HFMD (24). Notably, the percentage of Th17 cells was higher in the severe group compared with the mild group.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these findings, the imbalance of Th1/Th2 cells may stimulated by HFMD, while the Th17/Treg imbalance may play a decisive function in HFMD progression. These findings are consistent with a previous study by Chen et al, which identified that Th17 cells increased significantly in children with HFMD, suggesting that Th17-mediated immune response plays a crucial role in the progression of HFMD (24). Notably, the percentage of Th17 cells was higher in the severe group compared with the mild group.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that EV71 VLPs could not induce IL-23 production in human DCs and could not stimulate Th17 cell production in T cell cultures of MLR. Although we detected no IL-23 or IL-17 production, Chen et al recently demonstrated that the frequencies of Th17 cells and the number of neutrophils in peripheral blood samples from children infected with EV71 were significantly higher compared to controls [32]. In addition, higher levels of IL-17 and IL-23 were found in sera, but lower IFN-γ production was observed during EV71 infections.…”
Section: Discussioncontrasting
confidence: 86%
“…Studies suggested that the enhanced expression of IL-1, IL-6, IL-10, IL-13, IFN-γ and TNF-α is associated with life-threatening complications in severe HFMD cases [22][24], [26], [27]. A recent study has shown that IL-17 is involved in the pathological process of EV71 infection [28]. In our study participants, there was no difference between cases and controls during the stages of disease.…”
Section: Discussioncontrasting
confidence: 44%